Association of Infarct Volume Before Hemicraniectomy and Outcome After Malignant Infarction. - Lehrieder, Dominik; Layer, Katharina; Muller, Hans-Peter; Rucker, Viktoria; Kassubek, Jan; Juettler, Eric; Neugebauer, Hermann (Neurology, 2021)
OBJECTIVE: To determine the impact of infarct volume before hemicraniectomy in malignant middle cerebral artery infarction (MMI) as an independent predictor for patient selection and outcome prediction, we retrospectively analyzed data of 140 patients from a prospective multicenter study. METHODS: Patients from the Decompressive Surgery for the Treatment of Malignant Infarction of the Middle Cerebral Artery (DESTINY) Registry who underwent hemicraniectomy after ischemic infarction of >50% of the middle cerebral artery territory were included. Functional outcome according to the modified Rankin Scale (mRS) was assessed at 12 months. Unfavorable outcome was defined as mRS score of 4 to 6. Infarct size was quantified semiautomatically from CT or MRI before hemicraniectomy. Subgroup analyses in patients fulfilling inclusion criteria of randomized trials in younger patients (age ≤60 years) were predefined. RESULTS: Among 140 patients with complete datasets (34% female, mean [SD] age 54 [11] years), 105 (75%) had an unfavorable outcome (mRS score >3). Mean (SD) infarct volume was 238 (63) mL. Multivariable logistic regression identified age (odds ratio [OR] 1.08 per 1-year increase, 95% confidence interval [CI] 1.02-1.13, p = 0.004), infarct size (OR 1.27 per 10-mL increase, 95% CI 1.12-1.44, p < 0.001), and NIH Stroke Scale score (OR 1.10, 95% CI 1.01-1.20, p = 0.030) before hemicraniectomy as independent predictors of unfavorable outcome. Findings were reproduced in patients fulfilling inclusion criteria of randomized trials in younger patients. Infarct volume thresholds for prediction of unfavorable outcome with high specificity (94% in overall cohort and 92% in younger patients) were >258 mL before hemicraniectomy. CONCLUSION: Outcome in MMI depends strongly on age and infarct size before hemicraniectomy. Standardized volumetry may be helpful in the process of decision-making concerning hemicraniectomy.
EVALuna2:490728